2020
DOI: 10.1055/s-0040-1709154
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Revascularization: Current Practice and Future Directions

Abstract: Carotid stenosis is responsible for approximately 15% of ischemic strokes. Carotid revascularization significantly decreases patients' stroke risk. Carotid endarterectomy has first-line therapy for moderate-to-severe carotid stenosis after a series of pivotal randomized controlled trials were published almost 30 years ago. Revascularization with carotid stenting has become a popular and effective alternative in a select subpopulation of patients. We review the current state of the literature regarding revascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 95 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…Asymptomatic carotid artery stenosis (ACAS) is highly prevalent, associated with a low overall natural history risk, but is usually easily treated. Despite the low overall risk, >90% of carotid revascularization procedures in the US are performed in patients who are asymptomatic 8. Kim et al 9 reviewed the current evidence for asymptomatic carotid artery stenosis treatment strategies and important high risk features.…”
Section: Asymptomatic Carotid Artery Stenosis: a Summary Of Current S...mentioning
confidence: 99%
“…Asymptomatic carotid artery stenosis (ACAS) is highly prevalent, associated with a low overall natural history risk, but is usually easily treated. Despite the low overall risk, >90% of carotid revascularization procedures in the US are performed in patients who are asymptomatic 8. Kim et al 9 reviewed the current evidence for asymptomatic carotid artery stenosis treatment strategies and important high risk features.…”
Section: Asymptomatic Carotid Artery Stenosis: a Summary Of Current S...mentioning
confidence: 99%
“…Several trials have identified a risk reduction in stroke after CEA. This procedure has been recommended to patients presenting with 70%–99% stenosis (percentage of the arterial lumen blocked) in both the EU and the US, after three individual studies (the European Carotid Surgery Trial, the North American Symptomatic Carotid Endarterectomy Trial, and the Symptomatic Veterans Affair Cooperative Study Trial) identified a 16% reduction in absolute risk reduction, and ∼50% relative risk reduction from TIA after 5 years ( Bagley and Priest, 2020 ). Similarly, in asymptomatic carotid stenosis, two other studies (Asymptomatic Carotid Atherosclerosis Study and Asymptomatic Carotid Surgery Trial) on the use of CEA with a smaller percentage of stenosis revealed a statistically significant decrease in absolute risk, and a relative risk of stroke decrease by 4%–6% after 10 years ( Naylor, 2017 ).…”
Section: Current Treatmentsmentioning
confidence: 99%
“…Given its low prevalence and stroke risk, the United States Preventive Services Task Force currently recommends against screening for aCAS in the general adult population 3. Nevertheless, 90% of carotid revascularizations in the United States are performed on patients with aCAS 4 5…”
Section: Introductionmentioning
confidence: 99%